2005
DOI: 10.1007/s00442-005-0256-4
|View full text |Cite
|
Sign up to set email alerts
|

Root distribution and interactions between intercropped species

Abstract: Even though ecologists and agronomists have considered the spatial root distribution of plants to be important for interspecific interactions in natural and agricultural ecosystems, few experimental studies have quantified patterns of root distribution dynamics and their impacts on interspecific interactions. A field experiment was conducted to investigate the relationship between root distribution and interspecific interactions between intercropped plants. Roots were sampled twice by auger and twice by the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
233
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 343 publications
(262 citation statements)
references
References 28 publications
21
233
3
5
Order By: Relevance
“…Our previous study showed that faba bean has relatively shallow roots and a limited lateral root distribution, and few roots spread under maize plants, whereas the maize roots spread under faba bean plants in an intercropping situation (37). Therefore, we used root partition, as control, to eliminate root interactions between faba bean and maize.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that faba bean has relatively shallow roots and a limited lateral root distribution, and few roots spread under maize plants, whereas the maize roots spread under faba bean plants in an intercropping situation (37). Therefore, we used root partition, as control, to eliminate root interactions between faba bean and maize.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, via asymmetric facilitation, where one crop can alter the environment of the other positively, and enhance growth of the other species. This was observed in maize (Zea mays)-wheat (Triticum aestivum) intercrops, where maize facilitated growth and nutrient uptake in wheat, but not vice versa (Li et al 2006). Similarly, compounds released by chickpea (Cicer arietinum) roots enhanced root and shoot growth in wheat, but there was no apparent effect upon the chickpea (Wang et al 2007a).…”
Section: Plant Interspecific Competitionmentioning
confidence: 95%
“…However, few studies have been carried out to systematically compare the root distribution of crops when grown in combination, rather than as sole crops. This is largely due to the technical challenges involved in studies under field conditions, and the time and costs involved (Hauggaard-Nielsen et al 2001a;Li et al 2006). Where yield advantages are manifest, this is generally considered to be due to more efficient and complementary resource use, and largely attributed to belowground interactions and root facilitation (HauggaardNielsen and Jensen 2005).…”
Section: Plant Interspecific Competitionmentioning
confidence: 99%
“…Spatial complementarity can occur between two crop species with contrasting root architecture, leading to exploitation of different soil horizons (Li et al, 2006;C.C. Zhang et al, 2014; Fig.…”
Section: Observationsmentioning
confidence: 99%
“…1). For example, root compatibility between intercropped maize and associated faba bean allowed intercropped maize to spread underneath the roots of neighbouring faba bean, increasing the soil space exploited for nutrients and water (Li et al, 2006). Intercropped species with contrasting phenologies (Rose et al, 2007) and/or growth periods (e.g.…”
Section: Observationsmentioning
confidence: 99%